Development of activity of daily living modules based on behavioral approaches for moderate intellectual disability - Noorita Dwi Sulistyaningrum; Mumpuniarti Mumpuniarti; Nurkhamid Nurkhamid (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
Moderate intellectual disability requires a specific behavioral approach of learning Activity of Daily Living (ADL). This study aims to develop an appropriate and effective ADL module for moderate category intellectual disabilities in a special program instruction based on behavioral approaches. This research is a Research and Development (RD) using the Dick and Carey development model. The Dick and Carey development model consists of 10 steps of development, namely identifying needs in setting goals, analyzing learning, analyzing learners and context, developing learning objectives, developing assessment instruments, developing learning strategies, developing and selecting learning materials, designing and implementing formative evaluations, improving learning, designing and conducting the summative assessment. The module was implemented in the Special School of PGRI Sentolo and the Special School of Ma'arif Bantul through individual trials involving one subject, a small group trial involving six subjects, and a field test involving 15 subjects. Data collection was carried out using interviews, observations, questionnaires, and performance tests. The results of the study are that the ADL module is feasible and effective to use. The module was designed according to a behavioral approach, including the objectives were arranged from simple to complex, the presentation of the material was based on task analysis, verbal positive reinforcement was presented by the flap lift, and rewards are provided as star stickers available in the module.